La televisión nacional, comienzo contingente de una experiencia perdurable: el proceso de estatización de los canales de Buenos Aires (1973-1974) - Joaquín Sticotti (Nuevo mundo - Mundos Nuevos, 2020)
The aim of this article is to analyze the process of nationalization of Buenos Aires City’ TV channels (9, 11 and 13) between 1973 and 1974. For this aim, we take into account Television’s History from its origins until 1973 focusing on the role of State and the entrepreneurs. We also analyze decrees that determined the nationalization and public debates about the different projects for television through hemerographic material of the period. Our main hypothesis is that under the idea of a “national television” divergent projects struggle to impose: 1) a television at the service of the people, 2) a mixed system where private participation predominates, 3) a model of public service similar to the European, whose local application was never materialized. Finally, none of these projects prevails and television ends up under State control but holding a commercial model.